Managing, controlling, and improving quality - Montgomery, Douglas C.; Jennings, Cheryl L.; Pfund, Michele E. (Hoboken, New Jersey : John Wiley & Sons, 2011)
This book presents an organized approach to quality management, control, and improvement. Because quality problems usually are the outcome of uncontrolled or excessive variability, statistical tools and other analytical methods play an important role in solving these problems. However, these techniques need to be implemented within a management structure that will ensure success. This text focuses on both the management structure and the statistical and analytical tools. It organizes and presents this material according to many years of teaching, research, and professional practice across a wide range of business and industrial settings.
1. Introduction to quality -- 2. Management aspects of quality -- 3. Tools and techniques for quality control and improvement -- 4. Statistical inference about product and process quality -- 5. Control charts for variables -- 6. Control charts for attributes -- 7. Lot-by-lot acceptance sampling procedures -- 8. Process design and improvement with designed experiments -- 9. Reliability
Includes bibliographical references (p. 466-474) and index
Keywords: Educational change; Educational leadership; School management and organization